2015
DOI: 10.1098/rsta.2014.0225
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic computing: past, present and future

Abstract: We introduce and define 'heterotic computing' as a combination of two or more computational systems such that they provide an advantage over either substrate used separately. This first requires a definition of physical computation. We take the framework in Horsman et al. (Horsman et al. 2014 Proc. R. Soc. A 470, 20140182. (doi:10.1098/rspa.2014.0182)), now known as abstract-representation theory, then outline how to compose such computational systems. We use examples to illustrate the ubiquity of heterotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…The issue starts with Kendon et al [4], in which we extend our definition of physical computing [5] to include multiple substrates composed, in series or in parallel, into hybrid computational systems. We then flesh out what we mean by 'heterotic' computing through a collection of examples from quantum to biological.…”
mentioning
confidence: 99%
“…The issue starts with Kendon et al [4], in which we extend our definition of physical computing [5] to include multiple substrates composed, in series or in parallel, into hybrid computational systems. We then flesh out what we mean by 'heterotic' computing through a collection of examples from quantum to biological.…”
mentioning
confidence: 99%
“…Since 1786, bismuth has been used to treat gastrointestinal disorders such as gastritis, irritable bowel syndrome, constipation, peptic ulcer disease, and H pylori infection . Although it had antibacterial effects as well as a cyto‐protective effect on the gastric mucosa, the anti‐ H pylori effect of bismuth monotherapy had a low potency .…”
Section: Discussionmentioning
confidence: 99%
“…Since 1786, bismuth has been used to treat gastrointestinal disorders such as gastritis, irritable bowel syndrome, constipation, peptic ulcer disease, and H pylori infection. 7,[38][39][40] Although it had antibacterial effects as well as a cyto-protective effect on the gastric mucosa, the anti-H pylori effect of bismuth monotherapy had a low potency. 41 Previous studies suggested that bismuth might contribute studies conducted with bismuth subnitrate 11,13 were performed at least 20 years ago, when the resistance to antibiotics of H pylori was different compared to the nowadays.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson and Clark (2009), for example, note the importance of extended cognition in yielding ''hybrid processes in which the inner and the outer contributions are typically highly distinct in nature, yet deeply integrated and complementary' ' (p. 72). An appreciation of such complementarity is, of course, also evident in much of the literature pertaining to machine intelligence, especially work that goes under the heading of complementary computing , mixed-initiative systems (Horvitz 2007), interactive machine learning (Fogarty et al 2008) and heterotic computing (Kendon et al 2015). There is, however, a sense in which the notion of HEMC adds something new to this debate on complementarity.…”
Section: Extended Cognitionmentioning
confidence: 96%